Antifungal potential and defense gene induction in maize against Rhizoctonia root rot by seed extract of Ammi visnaga (L.) Lam. - RASHAD, Younes; ASEEL, Dalia; HAFEZ, Elsayed (Phytopathologia Mediterranea, 2018)
Methanol extracts from five medicinal plants (Eucalyptus tereticornis Sm., Ammi visnaga (L.) Lam., Azadirachta indica A. Juss., Rheum Palmatum L., and Adansonia digitata L.) were assessed in vitro for antifungal activity against Rhizoctonia solani Kühn, the causal agent of Rhizoctonia root rot of maize. All tested extracts showed antifungal activity with varied extents. Ammi visnaga (khella) extract showed the greatest activity compared with the untreated experimental controls. Observations using transmission electron microscopy showed ultrastructural changes in hyphal cells as a response to exposure to khella extract. Gas chromatography-mass spectrometric analysis of khella extract showed the presence of 69 compounds. The antifungal properties of the extracts were mainly attributed to their content of coumarins and fatty acids. In the greenhouse experiment, treatment of maize plants with khella extract at 15% gave the least incidence of Rhizoctonia root rot. Results of DD-PCR showed up- and down- regulations of some genes in maize as response to the treatment with khela extract. Identification of the randomly selected genes from DD-PCR revealed that they were defense-related, as S-domain class receptor-like kinase 3 and glutathione-S-transferase1. Real-time PCR showed induction in the gene expression of the pathogenesis-related protein chitinases (2.36 fold) and thaumatin-like proteins (8.99 fold) by treatment with khella extract at 15%, which was greater expression than detected at 10 and 20%. This indicates triggering effects from the extract on the maize immune system against the R. solani infection in a concentration-dependent manner. The efficient, low-cost and eco-friendly characteristics of khella extract indicate that it could be used for the control of Rhizoctonia root rot of maize.